The Relationship Between Time Management and Workload on Job Stress of High School Teachers in East Jakarta with Social Support as an Intervening Variable - Syamsudin, Syamsudin; Frimayasa, Agtovia (Jurnal Multidisiplin Sahombu, 2025)
This quantitative study aims to analyze the effect of Time Management and Workload on Job Stress among teachers, with Social Support as an intervening variable. Data were collected through a questionnaire survey distributed to 100 high school teachers in East Jakarta and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The outer model test results indicate that all indicators are valid and reliable, as shown by a loading factor above 0.70, an Average Variance Extracted (AVE) value above 0.50, and Composite Reliability exceeding 0.90. The R-Square values for the Social Support and Job Stress constructs are 0.897 and 0.886, respectively, indicating that both constructs can be comprehensively explained by the exogenous variables in the model. The key findings reveal that Workload and Time Management have a positive and significant effect on Job Stress, both directly and through Social Support. Interestingly, Social Support also exhibits a positive relationship with Job Stress, which may indicate increased expectations or role demands on teachers. This suggests that, rather than alleviating stress, a high level of social support may inadvertently increase psychological burdens. This study recommends further examination of the quality and type of social support provided to ensure that time management strategies and workload management effectively reduce teachers' Job Stress.